Implementasi N-Modular Redundancy Fault Tolerant System Pada Permodelan Automatic Train Protection - Ira Oktavianti; Rakhmadhany Primananda; Wijaya Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Automatic Train Protection System is a system to control the speed and braking of trains automatically, to avoid any obstacles that are read. Automatic Train Protection System belongs to the critical system category, if there is damage or error can affect the system as a whole. Thus, reliability is required in the critical system implementation, to obtain a high level of reliability and minimize the failure or Erorr level for the system to be able to persist. The level of reliability of the system can be done by implementing Hardware Redundancy. Redundancy is required as a data duplication using the N-Modular Redundancy method, to make the system fault tolerance and high reliability. The virtue in the application of redundancy lies in the microcontroller module used, such as Arduino UNO which acts as a module for the receiver of the Sharp Distance 2Y0A20 (Redundancy module) and the voter (voting) and LED modules (indicators Treatment). The liaison communication between the redundancy module and the voter can use I2C communication based on the prevailing rules. The test values of each module differ greatly from each module. Module C becomes a reliable module in the tolerance of test failures. The reliability percentage of the system without redundancy is 83.51% while with redundancy of 80.69% overall system.